Implementation of School Digital Libraries in Indonesia: A Systematic Review - Devi, Katrin Setio; Mazidah, Zahrina Roseliana; Nurkamilah, Siti; Kurniasih, Iridayanti; Ilmi, Bachrul; Saefullah, Rahmat Setiawan; Nurlistiani, Nurlistiani (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The purpose of this research is to identify the implementation of digital school libraries in Indonesia along with the obstacles in their implementation. This study used a systematic review method with planning, execution, and reporting stages. The databases used in this research were Google Scholar and Portal Garuda with a publication limit of the last 10 years (2013-2023). The search yielded a total of 169 articles. After the elimination process, a total of 9 articles were analyzed in this study. The results show that the majority of library implementations in Indonesia use web-based platforms with digital collection borrowing services obtained from free sources or the government. The obstacles in implementing digital libraries include limited budget, competent human resources, infrastructure, and digital library networking. This systematic review is expected to be used as a reference to determine further research agendas and considerations for schools in Indonesia that will implement a digital library system suitable for user needs.Keywords: digital library; school; implementation